The Wingate test in diagnostics of anaerobic efficiency at icehockey players - Szmatlan-Gabrys, U.; Gabrys, T.; Liberski, J.; Ficek, K. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The Wingate test then the used method often in control of anaerobic efficiency the ice hockey players` [Heller 2004, Schickhofer P., Hamar D. 1999] The objective of this study was to assess the changes of anaerobic capacity level in ice hockey players during 7-month games period on the background of values registered in the group of hockey players and I-st Team of Poland. Material and Methods.The study group included 23, icehockey players (19-20 year old), (Polish National Team. The assessment of anaerobic capacity with the use of the cycle ergometric test was carried out in Jun, September and December before the 3-week period preparation immediately before the World Championship. The control group consisted of 24 hockey players, members of Polish Olympic Team, who were subjected to similar testing procedure in December, after the completion of the 1st part of league play-offs. The following parameters were recorded during the test: maximal power (Pmax), average power (Pav), total work performed (WTOT), time-to-reach Pmax (Tuz), Pmax holding time (Tut). The lactate concentration in the blood (LA) was established before the test, then in 4th and 8th minute after the completion of the test. Results. The comparative analysis of ergometric parameters between groups of forward players revealed a number of changes in the characteristic of differences in the course of 7-month training period. After the special preparatory period (September) statistically significant changes were noted between the values of LAmax and DLA. In the analysed period, forward players improved their parameters of power and work and at the same time they improved their anaerobic metabolism. After intensive, consecutive period of preparation (December), insignificant decrease of Pmax and Wtot, as well as increased activation of anaerobic glycolysis was observed. High loads and intensity resulted in decreased level of abilities for undertaking work of anaerobic type. Considerable increment of energetic cost of this type of work was noted. These changes decreased the effectiveness of glycolytic anaerobic work. Conclusions.The obtained increment of power and total work performed was not adequate to the energetic cost. Therefore it may be hypothesised that excessive physical effort related to frequent participation of young players in hockey games may result in unfavourable changes as far as their adaptation to work of anaerobic character is concerned. The early recognition of unfavourable direction of metabolic adaptation remodelling, which occurs in response to accumulating training and competition loads, allows for a necessary correction of this training process.